PENGARUH PENGGUNAAN PUPUK HAYATI TERHADAP PERTUMBUHAN TANAMAN BELUM MENGHASlLKAN (TBM I) KOPI ROBUSTA (Coffea canephora Pierre ex Froehner) - Ahmad Junaedi; Ade Wachjar; Achirul Rahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
This experiment was aimed to study the effect of biofertilizer on growth of young Robusta coffee. New planting of Robusta coffee BP 42 x BP 358 was used with Randomized Complete Block Design and 3 replications. Treatments were fertilization as follows : P1 (20 g EMAS + 50 % recognized dosage of inorganic fertilizer (d.a.p.a.)), P2 (10 ml EM 4 + 50 % d.a.p.a.), P3 j (25 g OST + 50 % d.a.p.a.), P4 (5 kg manure + 50 % d a.p.a.) and P5 (d.a.p.a., 23 g Urea, 28 g SP36 and 16 g KCI). The results showed that sum couple, length and sum node of plagiotrophic stems were significantly different from 2 till 6 month after treatment, but it were not significantly different for height and stem diameter: Manure + 50 % d.a.p.a. was the best responses for all variables. EMAS + 50 % d.a.p.a. and EM 4 + 50 % d.a.p.a. had responses as good as inorganic fertilizer: Whereas, OST+ 50 % d.a.p.a. had the lowest responses for all variables.